Implikasi Fitrah Manusia dalam Pandangan Ilmu Pendidikan Islam - Wulandari, Fitri; Choiriyah, Irma; Maspuroh, Maspuroh; Zenal Mutaqin, Dadang (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
Human nature, according to Islamic teachings, is an innate state characterized by purity, faith, and monotheism, reflecting inherent potential that requires education to cultivate positive attributes. Islamic education, as a process of humanization, plays a central role in guiding humans to become vicegerents who can uphold divine values and achieve moral and intellectual balance. This study employs a qualitative method based on a literature review, analyzing books, journals, and other scientific sources to explore the relationship between human nature and the objectives of Islamic education. The findings indicate that Islamic education not only aims to preserve divine values but also to develop human potential so that individuals can contribute positively to society and their environment. Thus, Islamic education serves as a primary means to build individuals who harmonize spirituality and rationality in fulfilling their role in the world.